2016
DOI: 10.1111/jfpp.12925
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Textural Quality as a Parameter to Optimize Thermal Process During Retort Pouch Processing of Boneless Rohu Balls in Curry Medium

Abstract: Boneless fish ball from Rohu fish (Labeo rohita) in gravy packed in four-layered laminated retort pouch was processed in a steam/air mixture over-pressure retort at 121.1C to three different F 0 values of 6, 7 and 9 min. Time-temperature data were collected during heat processing using an Ellab Sterilization Monitoring System. Texture profiles such as hardness, springiness, gumminess and chewiness decreased as the F 0 value increased. Highest cohesiveness coincided with the highest score of texture. The L* val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…This could be attributed to the effect of increased heating time which imparted softening or brittle nature to the shrimp muscle due to the loosening of tissue muscle at higher processing time. A similar trend has been reported bySreenath et al (2007),Majumdar et al (2016),Shah et al (2017),Ali et al (2005),…”
supporting
confidence: 90%
See 1 more Smart Citation
“…This could be attributed to the effect of increased heating time which imparted softening or brittle nature to the shrimp muscle due to the loosening of tissue muscle at higher processing time. A similar trend has been reported bySreenath et al (2007),Majumdar et al (2016),Shah et al (2017),Ali et al (2005),…”
supporting
confidence: 90%
“…These plastic pouches have a thin profile of cross‐section that facilitates rapid heat penetration which will reduce the processing time and will lead to minimization in nutritional loss, improving product quality, and reducing energy requirement (Bindu et al., 2014; Rangarao, 2002). Literature on ready‐to‐eat fish and shrimp including analog shrimp products are available on rohu fish balls (Majumdar et al., 2016), freshwater prawn Macrobrachium rosenbergii (Majumdar et al., 2017); Indian white shrimp curry (Mallick et al., 2010), prawn kuruma (Mohan, 2004; Mohan et al, 2006, 2008), traditional Kerala style fish curry (Gopal et al., 2001), tilapia fish curry (Dhanapal et al, 2010); green mussel (Biji et al., 2015); analog shrimp and sous‐vide processed shrimp (Hema et al., 2020; Mohan et al., 2017; Remya et al., 2014), milk fish (Adepoju et al., 2017). Effect of high processing temperature on the quality in terms of nutritional as well as sensory attributes is a major concern to the thermal processing industries (Awuah et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Krzywdzinska-Bartkowiak et al [ 34 ] reported a decrease in shear force when beef was canned after salting and being cooked at a high temperature and pressure ( p < 0.05). Majumdar et al [ 35 ] manufactured a meat product, rohu balls, that were retorted at F 0 6, 7, and 9, and the hardness decreased as the F 0 increased ( p < 0.05). Ali et al [ 36 ] also reported decreased hardness with increased F 0 when canned sardines and pouches were manufactured according to F 0 of 5, 7, and 9.…”
Section: Resultsmentioning
confidence: 99%
“…Based on organoleptic and textural properties and the absence of viable microorganisms during storage, an F o value of 8 min with a total process time of 41.7 min at 121.1 °C was reported to be satisfactory for the preparation of Rohu fish curry in retort pouches. In a similar study, Majumdar et al [ 247 ] packaged boneless fish balls from Rohu fish in retort pouches and processed them in an overpressure retort at 121.1 °C to three different F o values of 6, 7 and 9 min. Based on commercial sterility, sensory evaluation, color and texture profile analysis, an F o = 7 min and a total process time of 42.21 min at 121.1 °C were found to be satisfactory for maintaining product quality.…”
Section: Innovative Seafood Preservation Methodsmentioning
confidence: 99%